(untitled) (African Journal of Biomedical Research, 2020)
While there has been worldwide focus on improving maternal mortality, in sub-Saharan Africa this is a challenge because of limited healthcare resources, inadequate health literacy and traditional beliefs. National and international policies emphasise better emergency maternal care, skilled birth attendants, better health education and community mobilization to ameliorate the situation. Evidence demonstrates the effect of skilled attendants, better education and emergency services but little about the impact of empowering local communities to take action to prevent maternal mortality. This concluding phase of a participatory action research project aimed to evaluate the actions of a rural community in southern Nigeria following mobilization towards prevention of maternal mortality. Twelve volunteers from the community directly or indirectly involved with pregnancy and childbirth were recruited through purposive and snowball sampling as co-researchers. They undertook participatory data collection from 8 focus groups and 12 individual interviews to evaluate actions previously undertaken by them to raise awareness about maternal mortality and its prevention. Data were thematically analysed. Findings presented in themes included: reported revised understandings of causes of maternal mortality rather than previous beliefs of attributing maternal complications/deaths to evil spirits; more appropriate behaviour to prevent maternal mortality such as preference of skilled birth attendants to traditional birth attendants. Conclusion is that through action research, the community appeared to have been mobilized by showing signs of empowerment to take action in collaboration with skilled birth attendants towards reduction of maternal mortality. Therefore, community members should be involved in actions that help to prevent maternal deaths